2013
DOI: 10.1111/jwas.12061
|View full text |Cite
|
Sign up to set email alerts
|

Spawning and Larval Development of the Four‐Sided Sea Cucumber, Isostichopus badionotus (Selenka 1867), under Controlled Conditions

Abstract: The objective of this study was to generate information for the development of Isostichopus badionotus culture protocols by determining optimal spawning methods, egg production, length and duration of larval stages, and larval habitat settlement preferences. Studies performed during the spawning seasons of 2010 and 2011 showed that this organism spawns between July and November without mechanical or chemical induction. The larval development has five well-defined stages: early, mid and late auricularia, doliol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 13 publications
2
38
1
Order By: Relevance
“…This might be a reasonable explanation for the relatively high nutritional value of the diatom Chaetoceros muelleri (fed live) reported during hatchery culture of sandfish from auriculariae to competent doliolariae (Knauer, 2011). Zacarías-Soto et al (2013) reported that a mixture of concentrated micro-algae from the Instant Algae® range (Tetraselmis and Isochrysis) can be used to raise the larvae of Isostichopus badionotus. In the current study, all commercially available micro-algae concentrates tested proved nutritious for H. scabra larvae when fed as single species, and all supported normal growth and development, and relatively high survival, through settlement.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This might be a reasonable explanation for the relatively high nutritional value of the diatom Chaetoceros muelleri (fed live) reported during hatchery culture of sandfish from auriculariae to competent doliolariae (Knauer, 2011). Zacarías-Soto et al (2013) reported that a mixture of concentrated micro-algae from the Instant Algae® range (Tetraselmis and Isochrysis) can be used to raise the larvae of Isostichopus badionotus. In the current study, all commercially available micro-algae concentrates tested proved nutritious for H. scabra larvae when fed as single species, and all supported normal growth and development, and relatively high survival, through settlement.…”
Section: Discussionmentioning
confidence: 96%
“…Hair et al (2011) reported successful larval culture of sandfish larvae when the majority of live micro-algae was replaced with concentrated micro-algae, while Zacarías-Soto et al (2013) more recently reported successful larval culture of Isostichopus badionotus using micro-algae concentrates alone. Broad use of commercially available micro-algae concentrates as food for sea cucumber larvae would support development of simplified larval rearing protocols that are more appropriate for developing nations.…”
Section: Introductionmentioning
confidence: 97%
“…These patches are characterized by high densities in central areas, with densities declining with distance from the center. This pattern could be very well a response of individuals to matting behavior (Zacarías-Soto et al, 2013) or to environmental conditions such as food availability (Slater et al, 2010(Slater et al, , 2011. Therefore, it will be important in future studies to include in the analysis factors such as substrate type, microalgae in sediments, organic matter, macroalgae, grain-size parameters of marine sediments, carbon concentration in sediments and other factors that influence sea cucumbers feeding behavior, or biochemical communication in reproductive behavior.…”
Section: Tablementioning
confidence: 98%
“…When the larvae reached the benthic stage, they were kept in the same tanks and fed with fresh C. muelleri and Thalassiosira weissflogii concentrate (Reed Mariculture, Inc. Campbell, CA, USA) followed by M. pyrifera and Sargassum sp. meals sieved at 55 µm enriched with Algamac 2000 (Bio‐Marine Inc. Hawthorne, CA, USA) and Spirulina powder (Zacarías‐Soto et al ) until juveniles were evident to the naked eye and developed the pigmentation pattern. The average weight at the beginning of the experiment was 0.24 ± 0.07 g.…”
Section: Methodsmentioning
confidence: 99%